2001
DOI: 10.1002/app.1800
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of additives: Grafting of itaconic acid onto LDPE by reactive extrusion. II. Effect of stabilizers

Abstract: Static and dynamic mixers set on the Brabender plastograph were used to investigate the grafting of itaconic acid (IA) onto low-density polyethylene (LDPE) by the reactive extrusion. The initiators of free-radical reactions were monoperoxide 2,5-dimethyl-2-hydroxy-5-tert-butylperoxy-3-hexyne and diperoxide 2,5-dimethyl-2,5-di(tert-butyl peroxy)-hexane. The reaction mix contained stabilizers of phenolic type as follows: 2,6-ditertbutyl-4-methyl phenol; ester of 3,5-ditert-butyl-4-hydroxyphenyl-propanoic acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Pesetskii et al investigated the grafting of itaconic acid onto PE and found that initiator solubility effects were more important than k d values [37] . Furthermore, free -radical inhibitors soluble in polyethylene but insoluble in itaconic acid inhibited crosslinking but did not signifi cantly affect grafting [38] .…”
Section: Effect Of the Initiatormentioning
confidence: 99%
“…Pesetskii et al investigated the grafting of itaconic acid onto PE and found that initiator solubility effects were more important than k d values [37] . Furthermore, free -radical inhibitors soluble in polyethylene but insoluble in itaconic acid inhibited crosslinking but did not signifi cantly affect grafting [38] .…”
Section: Effect Of the Initiatormentioning
confidence: 99%
“…The course of the main as well as the secondary processes depends much on the nature of the radical reaction's initiator and the reaction system's composition, as a whole. In particular, mutual dissolution of reactants in the polymer melt plays an important role in ensuring the grafted product output and in concurrent reactions, which include oligomerization of the monomer being grafted [10,11]. It may be expected that the adsorption of the initiator prepared with an active filler, or some other carrier, added to the reaction system will noticeably affect the course of the main and concurrent processes of PO functionalization.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, a number of investigations have been made in the field of chemical engineering and structural analysis of low-density polyethylene (LDPE), modified by grafting of itaconic acid (LDPEg-IA) in the course of reactive extrusion [7][8][9][10][11] as well as with carboxyl groups, which were neutralized by oxides or hydroxides of metals (LDPE-g-IA…”
Section: Introductionmentioning
confidence: 99%